Maternal satisfaction in private hospitals in Khyber Pakhtunkhwa, Pakistan / Um-E-Laila - Um-E-Laila, - (2018)
Maternal mortality remains unacceptably high in the developing world. Building a health care facility does not necessarily solve the problem, therefore the “quality of care” and “patient satisfaction” should be taken into consideration. While many factors can play a role, one important concern is whether the quality of service that is being offered to those who are using it meets their satisfaction level or not. This study was conducted to assess the satisfaction level of mothers with private health services in Khyber Pakhtunkhwa, and depicts the factors with which mothers are satisfied and dissatisfied. It identifies those factors which influences maternal satisfaction. It is a descriptive study with cross-sectional survey of 220 mothers who utilized private tertiary care health services in their current pregnancy. This study adopted a quantitative research approach, however to get a deeper insight, it also included the responses from mothers for the reasons of their reported level of satisfaction or dissatisfaction. The study was conducted at private sector hospitals in Peshawar, which is the capital city of Khyber Pakhtunkhwa. The sampling frame included mothers between the reproductive age of 18-49 years, who utilized the health services at the study setting in the month of November and December 2017. Non-probability, convenience sampling technique was used to select the private hospitals operating in Peshawar as the study setting. The subjects, having met the inclusion criteria, were selected from the mothers utilizing health services in private hospitals of Peshawar by convenience accessible sampling. This study used standardized PSQ-18 questionnaire to assess mother satisfaction with healthcare; which has been proven to have good reliability and internal consistency. Mothers satisfaction with health services in private hospitals was assessed based on seven factors of financial aspect, accessibility, convenience, technical quality, interpersonal manner, communication, and time spent with doctor. The results suggest that 39.5% of mothers were satisfied with the general or overall satisfaction while 55.9% were dissatisfied with the services of the private hospitals. Mothers were highly satisfied with the factors of interpersonal manner and convenience. Whereas, mothers were highly dissatisfied with the factors of communication and accessibility. Multiple regression analysis was performed to determine the main drivers of maternal satisfaction in Khyber Pakhtunkhwa. All seven factors emerged as statistically significant predictors of mother‟s satisfaction level in the current study, with technical quality as the most important predictor, followed by accessibility and interpersonal manner. The inclusion of all seven predictor variables in the final regression model yields 55.7% of variation in maternal overall satisfaction, which shows the model in substantial in nature. Educational level of mothers is entered in the regression model as a dummy variable, which also showed a significant yet inverse association with maternal satisfaction. This study showed that both process and structure attributes influences maternal satisfaction. The medical factor such as technical quality of care, provider‟s conduct; interpersonal manner, communication and time spent, and the non-medical factors; accessibility, convenience, and cost of care, all emerged as significant predictors of maternal satisfaction in Khyber Pakhtunkhwa, Pakistan.